Corrosion Inhibition of Zinc Metal in 2M Hydrochloric Acid Solution by Using GuaifenesinDrug as an Inhibitor and Theoretical Calculations - Adil, Hadeel (Al-Nahrain Journal of Science, 2018)
The inhibition of the corrosion of Zinc in 2 M HCl by guaifenesin has been investigated at room temperature using weight loss measurements. Results obtained showed that guaifenesin is a good inhibitor and its inhibition efficiency (IE %) increased with the increase of inhibitor concentration since it was 81%. At 300 ppm.The surface coverage was 0.81 at 300 ppm inhibitor concentration; hence the optimum concentration was 300 ppm.Theoretical calculations investigate by studying the relationship between molecular structure and inhibition efficiency by using semi-empirical molecular quantum calculations within the PM3 method as implemented in HyperChem package.